1978
DOI: 10.1159/000207758
|View full text |Cite
|
Sign up to set email alerts
|

Oxacillin-Induced Granulocytopenia

Abstract: The development of granulocytopenia during oxacillin therapy is reported in 2 patients. In both cases the onset of granulocytopenia occurred 24 days after therapy was instituted with similar clinical presentations. The bone marrow aspirates revealed myeloid hyperplasia, left shift and maturation arrest. 24 h after oxacillin was discontinued the granulocyte counts rapidly rose towards normal, with subsequent complete recovery. Although sought for, leukoagglutinins could not be demonstrated in either patient. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
1

Year Published

1979
1979
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
0
10
1
Order By: Relevance
“…I cannot agree with Fallon et al [1] that there is no published literature reporting the occurrence of granulocytopenia secondary to oxacillin therapy. Probably, the first case of oxacillin-induced neutropenia was reported by Freedman [2] in January 1965 in a 33-year-old woman following 272 months of therapy with oral oxacillin, 3 g/day.…”
contrasting
confidence: 66%
“…I cannot agree with Fallon et al [1] that there is no published literature reporting the occurrence of granulocytopenia secondary to oxacillin therapy. Probably, the first case of oxacillin-induced neutropenia was reported by Freedman [2] in January 1965 in a 33-year-old woman following 272 months of therapy with oral oxacillin, 3 g/day.…”
contrasting
confidence: 66%
“…Mechanisms on the pathophysiology of β-lactam-induced neutropenia have been proposed and like other causes of drug-induced neutropenia involve both a direct toxic effect inhibiting granulopoiesis and an immunologic reaction involving drug-induced or drug-dependent antibodies. 3,4,8,[10][11][12][13][14][15][16][17][18][19]68,69 Genetic variation causing predisposition to drug-induced neutropenia has been described and may play a role by increasing risk of a reaction to a specific agent. 70,71 A recent review of drug-induced agranulocytosis concluded that the available evidence supports an immunemediated mechanism as the primary pathogenesis.…”
Section: Pathogenesismentioning
confidence: 99%
“…Bone marrow studies generally reveal granulopoietic hypoplasia, secondary to the presence of immature granulocyte precursors, and apparent myeloid maturation arrest, presumably as a result of antibody-mediated destruction of mature myeloid cells. 1,8,10,12,20,68 Drug-induced neutropenia with a more rapid onset and resolution (<2 days) suggests peripheral neutrophil destruction by antineutrophil antibodies, whereas delayed resolution (2-7 days or longer) may indicate the presence of marrow toxicity and maturation arrest. Protracted recovery (14 days) may represent depletion of myeloid precursors.…”
Section: Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations